Teori Pajak Menurut Abu Yusuf Sebuah Alternatif Solusi Perpajakan di Indonesia - Rachmatullah Oky (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
Taxes are one of the sources of state opinion that has been formally used to sustain the development of a country. In this regard taxes may be said to be the main pillars of development, including the financing of civil servants, buying combat equipment, building infrastructure, etc. Unfortunately taxes taken from these people are often misused in its implementation as a support for development and are enjoyed only by a handful of people. Abu Yusuf, an economic thinker and also a faqih in the Abassiyah dynasty, has written the theory of this tax in his book Al-Kharaj which discusses the basis of the tax applied, and the reason for the use of funds in society so that it can be accountable. In this study, it will be known the things that pertain to the tax applied by Abu Yusuf which can be applied in modern human life today. Regarding the types of taxes and how they are applied in the present. So it can be a solution for a country to manage its income from taxes and use them in the best way.